Enhancing Education through Online Learning Management Systems - Sumathy. A,; Balasathuragiri.T, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The "Online Learning Management System" is an advanced web-based application designed to streamline the management of online classes for college students and educators. The system offers a user-friendly interface for students to easily access study materials, submit assignments, complete quizzes, and track their academic progress, thereby enhancing their overall learning experience. Teachers benefit from features that allow them to create and manage classes, upload various educational resources such as lectures, documents, and multimedia files, and evaluate student assignments. They can also monitor class sizes and manage course availability, optimizing course delivery and student engagement without the need for frequent face-to-face interactions. Administrative functionalities include managing teacher and student information, handling departmental and class details, and reviewing activity logs. This ensures efficient operation and oversight of the educational system, maintaining data accuracy and security. The system is developed with PHP for the front end, MySQL for the back end, and XAMPP as the web server, offering a reliable and scalable solution for academic management. Key features include real-time notifications, user-specific dashboards, and integrated communication tools. The application aims to improve academic management, facilitate seamless communication, and support a more organized and efficient educational environment.
Keywords: Online Learning Management System; Web Application; Academic Management; Student Portal; Teacher Portal; PHP; MySQL; XAMPP; Assignment Submission; Quiz Management; Educational Resources; Course Management; Administrative Functions; User Activity Logs